An Inconsistent ENSO Response to Northern Hemisphere Stadials Over the Last Deglaciation - Ryan H. Glaubke; Matthew W. Schmidt; Jennifer E. Hertzberg; Lenzie G. Ward; Franco Marcantonio; Danielle Schimmenti; Kaustubh Thirumalai (Geophysical Research Letters)
Abstract The dynamics shaping the El Niño‐Southern Oscillation's (ENSO) response to present and future climate change remain unclear, partly due to limited paleo‐ENSO records spanning past abrupt climate events. Here, we measure Mg/Ca ratios on individual foraminifera to reconstruct east Pacific subsurface temperature variability, a proxy for ENSO variability, across the last 25,000 years, including the millennial‐scale events of the last deglaciation. Combining these data with proxy system model output reveals divergent ENSO responses to Northern Hemisphere stadials: enhanced variability during Heinrich Stadial 1 (H1) and reduced variability during the Younger Dryas (YD), relative to the Holocene. H1 ENSO likely intensified through meltwater‐induced changes to ocean/atmospheric circulation, a response observed in models, but the lack of a similar response during the YD challenges model simulations. We suggest the tropical Pacific mean state during H1 primed ENSO for larger fluctuations under meltwater forcing, whereas the YD mean state likely buffered against it.